Ultrasonography in patients with chronic kidney disease - Chhetri, Pramod Kumar; Basnet, Subas Bahadur (Journal of Chitwan Medical College, 2021)
Background: Chronic kidney disease can be defined as kidney damage for > 3 months as evidenced by structural or functional abnormalities. Ultrasonography is the initial imaging modality employed in kidney disease. This study was undertaken to compare various sonographic parameters of the kidney with serum creatinine level and to establish the reliability of ultrasonography for estimating severity of kidney damage. Methods: This was a hospital based cross-sectional study on 60 patients with known chronic kidney disease who were advised for ultrasonography in the Department of Radiodiagnosis, COMS-TH during one-year period from Feb 2017 to Jan 2018. The serum creatinine level of each patients was compared subjectively to the renal cortical echogenicity. Other parameters like cortico-medullary differentiation and morphological parameters including kidney length, parenchyma thickness, and cortical thickness were also measured. Data analysis was done using SPSS 20.0 software program. The statistical correlations between sonographic parameters and serum creatinine were calculated using one-way analysis of variance (ANOVA) followed by Scheffe’s test. Results: Renal cortical echogenicity in patients with chronic renal disease showed a significant positive correlation with serum creatinine (F = 120.93; p<0.001). Other parameters like renal length (r = -0.933; p<0.001), parenchymal thickness (r = -0.945; p<0.001) and cortical thickness (r = -0.980; p<0.001) also showed significant but negative linear correlation with serum creatinine. Conclusions: Ultrasonography parameters like cortical echogenicity, renal length, parenchymal and cortical thickness can be used along with serum creatinine for estimating severity of renal damage in chronic kidney disease.